Management of Nagari Pariangan Tourism Village and The Economic Impact of The Nagari Pariangan Community in Tanah Datar District, West Sumatra Province - Suci, Artha Mevia Eka; Yurisman; Septriani (Kirana Publisher (KNPub), 2024)
This research discusses